Toward a theory of smart media usage: The moderating role of smart media market development - Biao Gao (AIMS Press, 2021)
Smart media usage is influenced by certain critical factors and can be further affected by the degree of diffusion in the market. However, existing research lacks sufficient understanding of the factors affecting smart media usage and their influential mechanisms. Taking AI-enabled smart TV in China as the research object, this study (1) develops a base model that includes users' three key gratifications (bi-directional communication, personalization, and co-creation); and (2) takes two sub-dimensions of market development (geographic segment and income segment) as moderators. Using data from 407 valid samples of current users, the partial least squares structural equation modeling analysis suggests that these three key smart gratifications can impact continuance intention with the moderating effect of market development. This study thus contributes to the literature by (1) clarifying the smart media gratification opportunities (smart media users' motivations or needs) for using smart media itself; (2) exploring the impact of the degree of market development on the uses and gratifications of the smart media itself; and (3) combining the uses and gratifications theory, and the diffusion of innovations theory, to complement each other in a model that provides a more complete picture of smart media usage.